2016
DOI: 10.1519/jpt.0000000000000042
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2 Different Exercise Approaches

Abstract: The findings from this study support the efficacy of the TC and Otago exercise programs in improving mobility in this sample of subjects. Furthermore, the Otago group showed greater improvement in lower extremity strength, whereas the TC group showed greater improvement in balance (OLS test). Also, the TC group showed a greater improvement in gait velocity after TC training program compared with the Otago exercise program. However, this study does not elucidate which exercise program is a more effective interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 34 publications
2
33
1
Order By: Relevance
“…A trial reported no benefit of Tai Chi on reducing falls relative to resistance exercise or usual care, but this study was underpowered for detecting a lower rate of falls relative to the resistance exercise (−15%) or usual care groups (−27%) (Woo, Hong, Lau, & Lynn, 2007). Other trials have reported similar benefits on several measures of physiological falls risk between Tai Chi and otago exercise (Son, Ryu, Jeong, Jang, & Kim, 2016) and between Tai Chi, yoga, and balance training (Ni et al, 2014). Another trial reported a greater reduction in falls and use of drug therapy among those with early or mild Parkinson's disease relative to generic exercise (aerobic, dance, and treadmill training; Li, Liu, Dai, & Dai, 2020).…”
Section: The Evidence For Tai Chi For Preventing Falls Relative To Otmentioning
confidence: 77%
“…A trial reported no benefit of Tai Chi on reducing falls relative to resistance exercise or usual care, but this study was underpowered for detecting a lower rate of falls relative to the resistance exercise (−15%) or usual care groups (−27%) (Woo, Hong, Lau, & Lynn, 2007). Other trials have reported similar benefits on several measures of physiological falls risk between Tai Chi and otago exercise (Son, Ryu, Jeong, Jang, & Kim, 2016) and between Tai Chi, yoga, and balance training (Ni et al, 2014). Another trial reported a greater reduction in falls and use of drug therapy among those with early or mild Parkinson's disease relative to generic exercise (aerobic, dance, and treadmill training; Li, Liu, Dai, & Dai, 2020).…”
Section: The Evidence For Tai Chi For Preventing Falls Relative To Otmentioning
confidence: 77%
“…The goal of this study was to determine the effectiveness of the program in a real-world setting. However, the OEP has been well studied in a variety of populations and a variety of settings (13, 15, 16, 37). Given this was a variation on an established model with evidence of effectiveness, there is ample opportunity to compare outcomes with published studies to determine the feasibility of this model for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, including systematic reviews with meta-analysis, recognize the OEP as an effective exercise prevention strategy with benefits in physical functioning and falls reduction ( Dadgari et al, 2016 ; El-Khoury et al, 2013 ; Liu-Ambrose et al, 2008 ; Robertson et al, 2002 ; Sherrington et al, 2017 ; Shier et al, 2016 ; Thomas et al, 2010 ), even in elderly stroke patients ( Park and Chang, 2016 ) and individual with age-related visual problems ( Kovács et al, 2012 ). Other studies also recognize benefits, but the results are not conclusive ( Binns and Taylor, 2011 ; Son et al, 2016 ).…”
Section: Introductionmentioning
confidence: 95%